2004
DOI: 10.1111/j.1365-2958.2004.04305.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of DNA into the medium by competent Streptococcus pneumoniae: kinetics, mechanism and stability of the liberated DNA

Abstract: SummaryThe release of chromosomal DNA into culture media has been reported for several naturally transformable bacterial species, but a direct link between competence development and the liberation of DNA is generally lacking. Based on the analysis of strains with mutations in competence-regulatory genes and the use of conditions favouring or preventing competence, we provide evidence that DNA release is triggered by the induction of competence in Streptococcus pneumoniae . Kinetic analyses revealed that where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
106
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 55 publications
(116 reference statements)
5
106
3
Order By: Relevance
“…In P. aeruginosa, eDNA release depends on quorum sensing (35), and there is evidence to suggest that cell lysis itself may be achieved by prophage induction within a biofilm (38,50), or alternatively, as a consequence of the release of membrane vesicles that contain bacteriolytic activity (51,52) as well as DNA (53). In Streptococcus mutans and Streptococcus pneumoniae, DNA is released from a lysing subfraction of the bacterial population in response to competence development, a physiological process that also depends on quorum sensing (54)(55)(56)(57)(58)(59). Both the actions of bacteriocins (59-61) and autolysins (56,58) have been implicated in the lysis of DNA-releasing cells during this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In P. aeruginosa, eDNA release depends on quorum sensing (35), and there is evidence to suggest that cell lysis itself may be achieved by prophage induction within a biofilm (38,50), or alternatively, as a consequence of the release of membrane vesicles that contain bacteriolytic activity (51,52) as well as DNA (53). In Streptococcus mutans and Streptococcus pneumoniae, DNA is released from a lysing subfraction of the bacterial population in response to competence development, a physiological process that also depends on quorum sensing (54)(55)(56)(57)(58)(59). Both the actions of bacteriocins (59-61) and autolysins (56,58) have been implicated in the lysis of DNA-releasing cells during this process.…”
Section: Discussionmentioning
confidence: 99%
“…In Streptococcus mutans and Streptococcus pneumoniae, DNA is released from a lysing subfraction of the bacterial population in response to competence development, a physiological process that also depends on quorum sensing (54)(55)(56)(57)(58)(59). Both the actions of bacteriocins (59-61) and autolysins (56,58) have been implicated in the lysis of DNA-releasing cells during this process. Intriguingly, a higher frequency of natural transformation was observed in S. mutans biofilm relative to planktonic cultures (62), and biofilm formation depends on the com system in both S. mutans (63) and S. pneumoniae (64).…”
Section: Discussionmentioning
confidence: 99%
“…Although this developmental process has been well studied for many decades, relatively little was known about how donor DNA was made available during competence development in the environment. A breakthrough in this field was made when it was shown, by measuring the release of either ␤-galactosidase (236,237), pneumolysin (Ply) (an intracellular ␤-hemolysin) (101), or chromosomal DNA (166,236,237) into the culture supernatant, that a lysing subpopulation of cells appeared during natural competence development in S. pneumoniae. The emergence of this lysing subpopulation is dependent on the ComCDE regulatory system (166,236,237) and results in the release of chromosomal DNA that could be used as a source of donor DNA for natural transformation (236).…”
Section: Fratricidementioning
confidence: 99%
“…A breakthrough in this field was made when it was shown, by measuring the release of either ␤-galactosidase (236,237), pneumolysin (Ply) (an intracellular ␤-hemolysin) (101), or chromosomal DNA (166,236,237) into the culture supernatant, that a lysing subpopulation of cells appeared during natural competence development in S. pneumoniae. The emergence of this lysing subpopulation is dependent on the ComCDE regulatory system (166,236,237) and results in the release of chromosomal DNA that could be used as a source of donor DNA for natural transformation (236). It was also shown by cocultivation experiments using mutants deficient in various components of the ComCDE system that two populations of cells are present during competence development: one population of competent, nonlysing cells that lyse the second population of noncompetent cells (101,237).…”
Section: Fratricidementioning
confidence: 99%
“…[16][17][18][19] Naturally transformable bacterial species release chromosomal DNA into culture media. [19][20][21][22][23] Extracellular bacterial DNA has also been proposed to play a role as a nutrient during starvation. In fact, previous studies have shown that Escherichia coli strains that consume DNA are more fit than those mutants unable to metabolize DNA.…”
mentioning
confidence: 99%